2007
DOI: 10.1103/physrevlett.98.165001
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence of a Zonal Magnetic Field in a Toroidal Plasma

Abstract: A zonal magnetic field is found in a toroidal plasma. The magnetic field has a symmetric bandlike structure, which is uniform in the toroidal and poloidal directions and varies radially with a finite wavelength of mesoscale, which is analogous to zonal flows. A time-dependent bicoherence analysis reveals that the magnetic field should be generated by the background plasma turbulence. The discovery is classified as a new kind of phenomenon of structured magnetic field generation, giving insight into phenomena s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 21 publications
(22 reference statements)
3
31
0
Order By: Relevance
“…However, while zonal electric fields and corresponding zonal flows are widely measured in experiments with properties that are consistent with the general theoretical framework (Diamond et al, 2005), zonal magnetic fields and currents, predicted theoretically (Chen et al, 2001;Diamond et al, 2005;Gruzinov et al, 2002;Guzdar et al, 2001b), have been only recently observed in experiments in the compact helical system (CHS) (Fujisawa et al, 2007).…”
Section: Nonlinear Excitation Of Zonal Structures By Toroidal Alfvén mentioning
confidence: 77%
“…However, while zonal electric fields and corresponding zonal flows are widely measured in experiments with properties that are consistent with the general theoretical framework (Diamond et al, 2005), zonal magnetic fields and currents, predicted theoretically (Chen et al, 2001;Diamond et al, 2005;Gruzinov et al, 2002;Guzdar et al, 2001b), have been only recently observed in experiments in the compact helical system (CHS) (Fujisawa et al, 2007).…”
Section: Nonlinear Excitation Of Zonal Structures By Toroidal Alfvén mentioning
confidence: 77%
“…Consequently, the fluctuation less than ϳ1 kHz should have symmetric structure around the magnetic field axis with a radial structure in mesoscale. 28 A constant phase relation between the signals from two different radial positions allows us to estimate the spatiotemporal characteristics of the zonal magnetic field in the radial direction by evaluating the correlation function, C͑⌬t , ⌬r͒ in exactly the same manner as that of the zonal flow. Figure 5͑b͒ shows the cross-correlation obtained by altering an observed position r 2 , shot by shot with fixing the other at r͑=12 cm͒.…”
Section: Identification Of Zonal Magnetic Fieldmentioning
confidence: 99%
“…27 The paper presents a brief review of the experimental achievements, using twin HIBPs in CHS, on the system of zonal flows and turbulence, together with the discovery of the zonal magnetic field. 28 The discovery is, to the authors' knowledge, the first evidence to show that the turbulence really generates the structured magnetic field, which is associated with a historical physics problem; i.e., the dynamo problem.…”
Section: Introductionmentioning
confidence: 98%
“…[2][3][4] The gyrokinetic simulations have also revealed that the ITG turbulence is regulated by self-generated zonal flows 5 of which existence is confirmed in a helical plasma experiment. 6 Contrary to the progress in the ion heat transport study, it is still difficult to explain the mechanism of anomalous electron heat transport. In a burning plasma, a large part of energy carried by fast alpha particles is absorbed by electrons.…”
mentioning
confidence: 96%